Case Report: Unveiling the hidden: a rare case of endometrial tuberculosis presenting as peritoneal carcinomatosis - Garci, Mariem; Makni, Mehdi; Abdelmoula, Ghada; Abdeljabbar, Amani; Babay, Wafa; Ben Saada, Nahla; Dhieb, Fatma; Hadj Kacem, Linda; Mathlouthi, Nabil; Belghith, Cyrine; Slimani, Olfa (Frontiers in Oncology, 2025)
BackgroundEndometrial tuberculosis (TB) is a rare form of extrapulmonary TB, particularly uncommon in postmenopausal women. Its atypical presentation, characterized by nonspecific symptoms, often leads to misdiagnosis, particularly when it is confused with malignancies. Moreover, peritoneal tuberculosis, although rare, can further complicate the diagnostic process due to its clinical manifestations that resemble those of various cancerous conditions. The coexistence of both endometrial and peritoneal TB in the same patient is particularly unusual and presents a significant diagnostic challenge.Case presentationWe report the case of a 49-year-old perimenopausal woman who presented with chronic pelvic pain, ascites, and postmenopausal bleeding. Initial imaging raised suspicion for peritoneal carcinomatosis. However, histopathological and microbiological investigations confirmed the diagnosis of endometrial and peritoneal tuberculosis. The diagnosis was established by the detection of acid-fast bacilli and granulomas in the biopsies from the endometrium and peritoneum. The patient was successfully treated with a standard anti-TB regimen, showing a favorable clinical response and gradual resolution of symptoms.ConclusionThis case underscores the importance of considering tuberculosis in the differential diagnosis of pelvic pathologies, particularly in endemic regions where TB is prevalent. It highlights the need for thorough investigation in cases of atypical pelvic symptoms in patients with risk factors, even in the absence of clear pulmonary symptoms. Including tuberculosis in the differential diagnosis could prevent misdiagnosis and allow for more prompt and appropriate management.